Covid Lockdowns in the UK: Estimating Their Effects on Transmission. Issue 2 (29th March 2022) - Prestige, Emily; Stander, Julian; Wei, Yinghui
Abstract: UK citizens have lived through three lockdowns over the course of the Covid-19 pandemic. What effect have these restrictions had on the transmission of the virus? Emily Prestige, Julian Stander and Yinghui Wei investigate